Predisposing factors to severe external root resorption associated to orthodontic treatment - Gracemia Vasconcelos Picanço; Karina Maria Salvatore de Freitas; Rodrigo Hermont Cançado; Fabricio Pinelli Valarelli; Paulo Roberto Barroso Picanço; Camila Pontes Feijão (Dental Press Editora, 2013)
OBJECTIVE: The aim of this study was to evaluate predisposing factors among patients who developed moderate or severe external root resorption (Malmgren's grades 3 and 4), on the maxillary incisors, during fixed orthodontic treatment in the permanent dentition. METHODS: Ninety-nine patients who underwent orthodontic treatment with fixed edgewise appliances were selected. Patients were divided into two groups: G1 - 50 patients with no root resorption or presenting only apical irregularities (Malmgren's grades 0 and 1) at the end of the treatment, with mean initial age of 16.79 years and mean treatment time of 3.21 years; G2 - 49 patients presenting moderate or severe root resorption (Malmgren's grades 3 and 4) at the end of treatment on the maxillary incisors, with mean initial age of 19.92 years and mean treatment time of 3.98 years. Periapical radiographs and lateral cephalograms were evaluated. Factors that could influence the occurrence of severe root resorption were also recorded. Statistical analysis included chi-square tests, Fisher's exact test and independent t tests. RESULTS: The results demonstrated significant difference between the groups for the variables: Extractions, initial degree of root resorption, root length and crown/root ratio at the beginning, and cortical thickness of the alveolar bone. CONCLUSION: It can be concluded that: Presence of root resorption before the beginning of treatment, extractions, reduced root length, decreased crown/root ratio and thin alveolar bone represent risk factors for severe root resorption in maxillary incisors during orthodontic treatment. OBJETIVO: avaliar os fatores comuns aos pacientes que desenvolveram reabsorção radicular externa moderada ou severa (graus 3 e 4 de Malmgren) nos incisivos superiores, durante o tratamento ortodôntico fixo na dentição permanente. MÉTODOS: foram selecionados 99 pacientes que iniciaram o tratamento ortodôntico fixo com a técnica Edgewise. Os pacientes foram divididos em dois grupos: G1 - 50 pacientes que concluíram o tratamento com ausência de reabsorções radiculares ou apresentando apenas irregularidades apicais (graus 0 e 1 de Malmgren), com idade média inicial de 16,79 anos e tempo de tratamento médio de 3,21 anos; G2 - 49 pacientes que finalizaram o tratamento apresentando reabsorção radicular moderada ou severa (graus 3 e 4 de Malmgren) nos incisivos superiores, com idade média inicial de 19,92 anos e tempo de tratamento médio de 3,98 anos. As radiografias periapicais e telerradiografias foram avaliadas, além de diversos fatores que pudessem influenciar a ocorrência de uma reabsorção severa. A análise estatística incluiu o testes qui-quadrado, teste exato de Fisher e teste t independente. RESULTADOS: foi demonstrada a presença de diferença significativa entre os grupos para as variáveis realização de extrações, grau de reabsorção radicular inicial, comprimento radicular, proporção coroa/raiz e da espessura da cortical óssea alveolar. CONCLUSÃO: pode-se concluir que são fatores de risco para reabsorção radicular severa nos incisivos superiores, durante o tratamento ortodôntico, a presença de reabsorção radicular antes do início do tratamento, a realização de extrações, o comprimento radicular reduzido, a proporção coroa/raiz diminuída e a espessura óssea alveolar fina.